2011
DOI: 10.1007/s10482-011-9669-8
|View full text |Cite
|
Sign up to set email alerts
|

Phyllosphere bacterial communities of trichome-bearing and trichomeless Arabidopsis thaliana leaves

Abstract: This study aimed to investigate whether the presence of trichomes as conspicuous physical attributes of the leaf surface affects the microbial community composition on Arabidopsis thaliana leaves. The A. thaliana ecotype Col-0 and its trichomeless gl1 mutant were grown in growth cabinets under climate-controlled conditions. The gl1 mutant showed a similar wax composition as the Col-0 wild type with slightly reduced amounts of C(29), C(31) and C(33) alkanes by GC/MS and GC/FID analyses. 120 bacterial isolates r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…The total wax load and composition per surface area described in this study for this mutant closely matched published values for wild-type leaves (Lü et al, 2009;Bourdenx et al, 2011) and supports previous findings where gl1 was shown to have relatively small differences in wax composition per fresh weight as compared with the wild type (Xia et al, 2010). Moreover, the leaf wax composition in this study parallels that found by Reisberg et al (2012), assuming they grouped straight and branched alcohols together.…”
Section: Discussionsupporting
confidence: 90%
“…The total wax load and composition per surface area described in this study for this mutant closely matched published values for wild-type leaves (Lü et al, 2009;Bourdenx et al, 2011) and supports previous findings where gl1 was shown to have relatively small differences in wax composition per fresh weight as compared with the wild type (Xia et al, 2010). Moreover, the leaf wax composition in this study parallels that found by Reisberg et al (2012), assuming they grouped straight and branched alcohols together.…”
Section: Discussionsupporting
confidence: 90%
“…However, consistent among all plants, regardless of growth conditions, was the predominance of the Proteobacteria and Firmicutes phyla. These phyla comprise the majority of bacteria in the phyllosphere of other agricultural and native plant species (8, 11, 13, 14, 30). This result is notable, given the likelihood that the plants in the agricultural field were likely exposed to very different bacterial species than those in the environmental chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the primary function of cuticles is to limit nonstomatal water loss and, thus, to protect plants against drought stress (Burghardt and Riederer, 2006). However, plant cuticles also play roles in minimizing the adhesion of dust, pollen, and spores (Barthlott and Neinhuis, 1997), protecting tissues from UV radiation (Krauss et al, 1997;Solovchenko and Merzlyak, 2003), mediating biotic interactions with microbes (Carver and Gurr, 2006;Leveau, 2006;Hansjakob et al, 2010Hansjakob et al, , 2011Reisberg et al, 2012) as well as insects (Eigenbrode and Espelie, 1995;Müller and Riederer, 2005), and preventing deleterious fusions between different plant organs (Tanaka and Machida, 2013).…”
mentioning
confidence: 99%